ART AS A CULTURAL INSTRUMENT: THE ROLE OF ACEHNESE ART IN RESOLVING HORIZONTAL CONFLICT - Dhuhri, Saifuddin (Jurnal Ilmiah Peuradeun, 2016)
This article begins with explaining the present problems of Acehnese cultural identity, then articulating how the art is usefully employed to solve those difficulties. Relying on post-colonial theories, I formulate the framework that Acehnese art has significant position to handling current cultural problem of Acehnese society. This work offers a cultural resolution of Acehnese present conflict between traditionalist and modernist Muslims, which are represented by Dayah and Muhammadiyah community in Aceh. It is commonly known that Islam is the pride of the Acehnese. To date, there is, however, no certainty about the nature of Islam in Aceh, as heated debate still exists between traditionalist and modernist Muslims upon the nature of Sharia application in the place. This dispute has generated different extreme perspectives upon seeing themselves in the way to treat their cultural identity. Here we establishes that Acehnese art plays great role in bringing togetherness to different groups of Acehnese society, which results in resolving horizontal conflict of Acehnese society. It shows that Acehnese art accommodates to all of different ness of Acehnese communities and, therefore, raises Acehnese collective consciousness.